2011
DOI: 10.1002/app.34047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretic studies on sound transmission loss of laminated mica‐filled poly(vinyl chloride) composites

Abstract: The effects of dioctyl phthalate and inorganic filler, mica, on the sound insulation property of poly(vinyl chloride) (PVC) were investigated in this work. The stiffness and mass laws, which are the common theoretic tools to predict the soundproof properties of materials, were used to analyze the sound transmission loss (STL). The experimental results revealed that the stiffness and mass laws can describe well the sound insulation property of PVC/mica composites. The stiffness and surface density are important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…For example, the foam density of the epoxy foam with 6 wt% microsphere content drastically decreases to only 0.46 × 10 3 kg/m 3 . Base on the mass law of acoustics, too low foam density is rather detrimental to the sound TL .…”
Section: Resultsmentioning
confidence: 99%
“…For example, the foam density of the epoxy foam with 6 wt% microsphere content drastically decreases to only 0.46 × 10 3 kg/m 3 . Base on the mass law of acoustics, too low foam density is rather detrimental to the sound TL .…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [60] conducted an experimental study and revealed that the stiffness and mass laws well described the sound insulation property of polyvinyl chloride (PVC)/mica composites. Predictions models are also used in estimating sound transmission loss of multilayer structures.…”
Section: Sound Insulationmentioning
confidence: 97%
“…To this end, barite (BaSO 4 ) and magnetite (Fe 3 O 4 ) are commonly used. Besides, different kinds of inorganic fillers such as carbon black, nanoclay, mica , and calcite (CaCO 3 ) , though having low solid density, are also utilized. In spite of diversity in inorganic fillers, there is no study in the literature, in which hematite (Fe 2 O 3 ) is used as an inorganic filler for sound damping purposes.…”
Section: Introductionmentioning
confidence: 99%